Paradoxes of Malaysian literature and "collective individuality" in theorising national identity - Omar, Noritah (Universiti Putra Malaysia Press, 2014)
After 56 years of Independence, Malaysia still continues to struggle with its efforts in constructing an amicable â€˜national identity.â€™ The struggle especially centred on the â€˜one nation one languageâ€™ policy, which later led to another contentious determinant of national identity, that of â€˜national literature.â€™ Malaysian literature, due to the nationâ€™s colonial experience, consequentially falls under the category of â€˜postcolonial literature.â€™ This comes with its attendant baggage of also being considered as peripheral literature, or emergent literature, or Third World literature. In other words, it is categorically non-western literature. The question this gives rise to is: which direction should Malaysian literature take in asserting a â€˜trueâ€™ postcolonial identity? Should it continue to be one that insists on reinforcing the â€˜one nation one languageâ€™ ideal with modern Malay literature (written by predominantly Malay writers) representing collectively the nationâ€™s identity? Or should it recognize those strong voices of dissent as the â€˜true postcolonialâ€™, those voices of (especially) non-Malay writers who insist on writing in the language of the coloniser (English)? This paper considers these positions by using the German Romantic ideal of â€œcollective individualityâ€ as its measure of how far Malaysian literature (represented by both modern Malay literature and Malaysian literature in English) has truly come to its own as worthy of being called â€˜postcolonialâ€™ literature. In doing so, the paper also highlights the problematic term â€˜national literature.â€™